Capacitação do médico para comunicar más notícias à criança - Perosa, Gimol Benzaquen [UNESP]; Ranzani, Priscila Moreci [UNESP] (Associação Brasileira de Educação Médica, 2008)
The movement toward humanization of medicine stimulated new studies about inclusion of controversial subjects in the curriculum of the medical courses and alternative strategies for qualifying the future professionals. The present study investigated the opinion of physicians that attend children with respect to how they convey information about diseases of uncertain prognosis. The study also analyzed how these professionals were equipped to exercise this function, aiming to include in the curriculum strategies that help future doctors to cope with these situations. Fifty-three pediatricians responded a semi-structured questionnaire. The majority of the sample believed that children have the right to such information; 70% had already been exposed to this kind of situation. Independently how long ago they graduated, 48% had discussed the subject during medical school and residency but only 30% acknowledged having had specific training on this subject. Older physicians reported that they had learned by observing professionals with whom they worked. The article discusses the need of considering new teaching strategies such as role-playing for issues that, in addition to the scientific knowledge, involve emotional, ethical and legal aspects.

O movimento de humanização na saúde impulsionou pesquisas sobre a inclusão de assuntos polêmicos nos currículos médicos, assim como de estratégias inovadoras para capacitar futuros profissionais. Com o objetivo de incluir no currículo atividades que habilitem os alunos de medicina a enfrentar situações difíceis, este estudo investigou a opinião de médicos que atendem crianças a respeito de como dar à criança informações sobre doenças de prognóstico incerto e como os profissionais se instrumentaram para enfrentar essas situações. Para tanto, 53 médicos responderam a um questionário semi-estruturado. A maioria dos médicos opinou que a criança tem direito a essas informações e 70% da amostra já haviam enfrentado essa situação. Independentemente do tempo de formados, 48% dos sujeitos discutiram o assunto na graduação e residência, mas apenas 30% relataram ter recebido habilitação específica. Os médicos mais velhos disseram ter aprendido observando modelos. Discute-se a necessidade de contemplar novos conhecimentos científicos e novas estratégias de aprendizagem, como o role-playing, para tópicos que, ao lado do conhecimento científico, envolvem fatores emocionais e de ordem ética e legal.
Enabling physicians to communicate bad news to children
Keywords: Communication; Doctor-patient relation; Education, medical; Child, hospitalized; Comunicação; Relações médico-paciente; Educação médica; Criança hospitalizada